పత్రికలు - ప్రసార మాధ్యమాలు తెలుగు - Chennaiah, J. (Visalandhra Book House, Telangana, 2010)
This book is all about newspapers and broadcasting channels
Patrikalu Prasara Madhyamalu-Telugu
Keywords: Telugu; పత్రికలు – ప్రసార మాధ్యమాలు తెలుగు; Patrikalu Prasara Madhyamalu-Telugu; Media Literature; Telugu; Telugu